The BR signaling pathway regulates primary root development and drought stress response by suppressing the expression of PLT1 and PLT2 in Arabidopsis thaliana - Zhao, Zhiying; Wu, Shuting; Gao, Han; Tang, Wenqiang; Wu, Xuedan; Zhang, Baowen (Frontiers in Plant Science, 2023)
With the warming global climate, drought stress has become an important abiotic stress factor limiting plant growth and crop yield. As the most rapidly drought-sensing organs of plants, roots undergo a series of changes to enhance their ability to absorb water, but the molecular mechanism is unclear. Here, we found that PLT1 and PLT2, two important transcription factors of root development in Arabidopsis thaliana, are involved in the plant response to drought and are inhibited by BR signaling. PLT1- and PLT2-overexpressing plants showed greater drought tolerance than wild-type plants. Furthermore, we found that BZR1 could bind to the promoter of PLT1 and inhibit its transcriptional activity in vitro and in vivo. PLT1 and PLT2 were regulated by BR signaling in root development and PLT2 could partially rescue the drought sensitivity of bes1-D. In addition, RNA-seq data analysis showed that BR-regulated root genes and PLT1/2 target genes were also regulated by drought; for example, CIPK3, RCI2A, PCaP1, PIP1;5, ERF61 were downregulated by drought and PLT1/2 but upregulated by BR treatment; AAP4, WRKY60, and AT5G19970 were downregulated by PLT1/2 but upregulated by drought and BR treatment; and RGL2 was upregulated by drought and PLT1/2 but downregulated by BR treatment. Together, our findings not only reveal the mechanism by which BR signaling coordinates root growth and drought tolerance by suppressing the expression of PLT1 and PLT2 but also elucidates the relationship between drought and root development. The current study thus provides an important theoretical basis for the improvement of crop yield under drought conditions.